2014
DOI: 10.3141/2408-06
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Roller-Compacted Concrete Pavement in the Fayetteville Shale Play Area, Arkansas

Abstract: In 2012, roller-compacted concrete (RCC) pavement was used to rehabilitate a deteriorated section of roadway in the Fayetteville Shale Play Area (FSPA), Arkansas. As the result of recent heavy truck traffic related to natural gas exploration efforts in Arkansas, the FSPA has experienced significant pavement distresses that typical maintenance activities cannot sufficiently address. RCC pavement was selected as a potential solution to repair failing pavements in this area because that pavement could be construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…SSB, barajlar, kereste depoları, ağır nakliye yolları, yükleme rıhtımları, liman tesisleri ve otoparklar gibi çeşitli uygulamalarda uzun yıllardır kullanılmaktadır. Son zamanlarda, SSB karışımları, şehir sokakları, otoyollar ve şehirlerarası yollar olmak üzere karayolu uygulamalarında daha yaygın hale gelmiştir [3].…”
Section: A Avantajlari Ve Dezavantajlariunclassified
“…SSB, barajlar, kereste depoları, ağır nakliye yolları, yükleme rıhtımları, liman tesisleri ve otoparklar gibi çeşitli uygulamalarda uzun yıllardır kullanılmaktadır. Son zamanlarda, SSB karışımları, şehir sokakları, otoyollar ve şehirlerarası yollar olmak üzere karayolu uygulamalarında daha yaygın hale gelmiştir [3].…”
Section: A Avantajlari Ve Dezavantajlariunclassified
“…Traditionally, the critical cracking failure for a rigid pavement would be the cracks initiated at the bottom of the rigid layer due to repeated fatigue loading. However, field observations of cores and trench sections from in-service pavements have shown that premature failures may develop from the surface and propagate their way down, such as top-down cracking [26][27]. Recently, it was found that the crack could also initiate from the near-surface of rigid pavements.…”
Section: Analysis Of Cracking Potentials Of Thin Rcc Pavementsmentioning
confidence: 99%
“…The compressive strengths, when removing the fly ash, were more than 5,000 pounds per square inch (psi) for both sections. The cost analysis showed that Arkansas may have saved upward of $1 million per mile through the use of RCC rather than traditional full-depth reclamation and an asphalt surface (7).…”
Section: Laboratory Evaluation and Field Construction Of Roller-compactedmentioning
confidence: 99%